2019
DOI: 10.1002/nop2.387
|View full text |Cite
|
Sign up to set email alerts
|

“The meal is an activity involving at least two people”—Experiences of meals by older persons in need of elderly care

Abstract: AimA shift of focus on older persons’ nutrition has occurred, from focusing on nutrition status to focusing on the whole meal. There is lack of studies on how older persons experience meals. Knowledge is needed to enhance a meal with dignity and pleasure, but also to prevent deterioration in nutrition. The aim was to describe meals from the perspective of older persons in need of elderly care.DesignA descriptive qualitative study.MethodSemi‐structured interviews (N = 18) were conducted and analysed using thema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This review also supports the findings of previous studies regarding the importance of social relations and commensality during mealtimes for patients in hospitals and nursing homes (58‐63). Markovski et al showed that older inpatients consumed 20% more energy and protein when eating in a communal dining room, which emphasises the importance of commensality during mealtimes.…”
Section: Discussionsupporting
confidence: 88%
“…This review also supports the findings of previous studies regarding the importance of social relations and commensality during mealtimes for patients in hospitals and nursing homes (58‐63). Markovski et al showed that older inpatients consumed 20% more energy and protein when eating in a communal dining room, which emphasises the importance of commensality during mealtimes.…”
Section: Discussionsupporting
confidence: 88%
“…This effect has also been found to increase food intake in a study including orthopedic inpatients [18]. The same association was also found in a questionnaire survey in a group of Swiss patients [19] and a qualitative survey made in Swedish nursing home residents [17]. The participants from the Swiss study had to choose their meals from a variety of food choices.…”
Section: Patient Autonomysupporting
confidence: 63%
“…In a group of nursing home residents in Sweden, it was found that the participants wished to have the possibility to decide the menu [17]. Furthermore, a higher degree of participation in the practical aspects of the meal was warranted [17]. Each day, the patients of the current pilot study were free to shape their own menu.…”
Section: Patient Autonomymentioning
confidence: 96%
See 1 more Smart Citation
“…Several researchers have illustrated eating habits and meal experiences from different perspectives and focuses in recent decades (Bourdieu 1984;Hansen 2016;Meiselman 2000Meiselman , 2003Odencrants et al 2020;Piqueras-Fiszman and Spence 2014). The research is varied and has examined older consumers from different approaches (Deierlein et al 2014;Jonsson et al 2020;Liu et al 2014).…”
Section: Introductionmentioning
confidence: 99%